Fibonacci Numbers – Sum of Odd Fibonacci Numbers

combinatoricsfibonacci-numbers

Trying to prove that the sum of odd-index consecutive Fibonacci numbers is the next even-index Fibonacci number. I have a gap in my proof that I cannot figure out. I know that induction would be easier and I have already done it that way, I am looking to use alpha and beta.
$$\sum_{i=1}^n F_{2i-1} = F_{2n}$$

$$\begin{align*}
\sum_{i=1}^n F_{2i-1}&=\sum_{i=1}^1 \frac{1}{\sqrt{5}}(\alpha^{2i-1}-\beta^{2i-1})\\
&=\frac{1}{\sqrt{5}}\left(\sum_{i=1}^1\alpha^{2i-1}-\sum_{i=1}^1\beta^{2i-1}\right)\\
&\;\;\vdots\\
&=\frac{1}{\sqrt{5}}[(\alpha^n-\beta^n)(\alpha^n+\beta^n)]\\
&=\frac{1}{\sqrt{5}}(\alpha^{2n}-\beta^{2n})\\
&=F_{2n}
\end{align*}$$

Best Answer

HINT: Induction is much easier, but if you really must use Binet’s formula, note that your summations are geometric, with ratios $\alpha^2$ and $\beta^2$, respectively; you can use the familiar formula for the sum of a finite geometric series. You also know that $\alpha$ and $\beta$ satisfy the equation $x^2-x-1=0$, so $\alpha^2-1=\alpha$ and $\beta^2-1=\beta$; this information will help you simplify the sums of the geometric progressions.

Related Question